THE MODEL OF DEFINITION FOR THE ACCRUAL RATE ASSESSMENT OF THE REQUIRED NUMBER OF PERSONNEL FOR THE COMBAT DUTY TASKS FOR THE CERTAIN FACILITIES SECURITY - Gorodnov, V. P.; Sukonko S. М. (Honor and Law, 2019)
The model of calculation proposed in order to determine factors for the assessment of the required number of personnel needed with all known features of modern conditions of service on the certain facilities.